The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/pac-2016-1018
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light activated photocatalytic effect of glass and glass ceramic prepared by recycling waste slag with hematite

Abstract: Abstract A relationship between the local structure and the visible-light activated photocatalytic effect was investigated in the glass and glass ceramics prepared by recycling waste slag, which was discharged from a Tokyo Household Garbage Combustion Plant. For the preparation of a homogeneous sample of waste slag recycled glass, (WSRG), 10 wt% of Na2CO3 and 10–50 wt% of Fe2O3 were added. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The compositions of CWS are similar to iron-containing silicate glasses, for which the photocatalytic effect has previously been observed [5]. To date, CWS is used in civil engineering works as a low-value base material or aggregate for the construction of roads and concretes so new applications and new opportunities for valorization and recycling of CWS is essential from both economic and environmental perspectives.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The compositions of CWS are similar to iron-containing silicate glasses, for which the photocatalytic effect has previously been observed [5]. To date, CWS is used in civil engineering works as a low-value base material or aggregate for the construction of roads and concretes so new applications and new opportunities for valorization and recycling of CWS is essential from both economic and environmental perspectives.…”
Section: Introductionmentioning
confidence: 60%
“…Iida et al [9] reported that iron alumino-silicate glass, to CWS, showed a photocatalytic effect after heat treatment at 1000 °C for 100 min, with a k (pseudo-first-order rate constant) of 9.26 × 10 −3 min −1 for MB degradation. Ishikawa et al [5] reported that heat treatment of waste slag recycled glass-ceramics (WSRG) with In our previous work [11], we succeeded in preparing glass and glass-ceramics from CWS by melt-quenching, obtaining k values of up to 2.2 × 10 -2 min -1 by melting the slag at 1400 °C, then subsequently heat treating it at 800 °C for 100 min. Here we aim to enhance the results achieved by melt quenching by introducing a facile method for using DSW as a photocatalytic material by treating as-collected DSW with HNO 3 and applying the photo-Fenton reaction under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that R-NaWSFex heattreated at the higher temperature has a higher photocatalytic ability which depends on kinds and amounts of the precipitated crystalline phases. In our previous study, we could observe a k value of 2.65•10 -3 min -1 for a glass-ceramics prepared from Na 2 O+domestic waste slag+xFe 2 O 3 by melting at 1400 o C for 1 h and heat-treated at 800 o C for 100 min [8]. By comparing the largest k value obtained for R-NaWSFe30 heat-treated at 900 o C in this study(=(9.75±0.01) •10 -3 min -1 ) and that obtained for the glass-ceramics prepared from existing domestic waste slag(=2.65•10 -3 min -1 ), it can be said that much more effective photocatalytic material can be prepared by isolating impurity from existing domestic waste slag.…”
Section: Uv-vis Spectramentioning
confidence: 90%
“…Glass and ceramics produced from domestic waste model slag with different iron concentration, denoted as model-slag+10Na 2 O+xFe 2 O , abbreviated as (R-NaWSFex, x = 10, 30, mass%) were prepared by melt quenching method. The chemical composition of the model slag was based on the previously reported values [8] The prepared glasses and glass-ceramics containing model slag plus additions, before and after heat-treatment were characterized by X-ray diffractometry (XRD), 57 Fe-Mössbauer spectroscopy and ultra-violet visible-light absorption spectroscopy (UV-VIS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation